Artd1/Parp1 Regulates Reprogramming by Transcriptional Regulation of Fgf4 Via Sox2 ADP‐Ribosylation. (November 2013) - Weber, Fabienne A.; Bartolomei, Giody; Hottiger, Michael O.; Cinelli, Paolo
Abstract The recently established reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) by Takahashi and Yamanaka represents a valuable tool for future therapeutic applications. To date, the mechanisms underlying this process are still largely unknown. In particular, the mechanisms how the Yamanaka factors (Oct4, Sox2, Klf4, and c‐Myc) directly drive reprogramming and which additional components are involved are still not yet understood. In this study, we aimed at analyzing the role of ADP‐ribosyltransferase diphtheria toxin‐like one (Artd1; formerly called poly(ADP‐ribose) polymerase 1 [Parp1]) during reprogramming. We found that poly(ADP‐ribosylation) (PARylation) of the reprogramming factor Sox2 by Artd1 plays an important role during the first days upon transduction with the reprogramming factors. A process that happens before Artd1 in conjunction with 10–11 translocation‐2 (Tet2) mediates the histone modifications necessary for the establishment of an activated chromatin state at pluripotency loci (e.g., Nanog and Essrb) [Nature 2012;488:652–655]. Wild‐type (WT) fibroblasts treated with an Artd1 inhibitor as well as fibroblasts deficient for Artd1 (Artd1−/−) show strongly decreased reprogramming capacity. Our data indicate that Artd1‐mediated PARylation of Sox2 favors its binding to the fibroblast growth factor 4 (Fgf4) enhancer, thereby activating Fgf4 expression. The importance of Fgf4 during the first 4 days upon initiation of reprogramming was also highlighted by the observation that exogenous addition of Fgf4 was sufficient to restore the reprogramming capacity of Artd1−/− fibroblast to WT levels. In conclusion, our data clearly show that the interaction between Artd1 and Sox2 is crucial for the first steps of the reprogramming process and that early expression of Fgf4 (day 2 to day 4) is an essential component for the successful generation of iPSCs. Stem Cells2013;31:2364–2373